Euthanasia and Physician-Assisted Suicide in People With an Accumulation of Health Problems Related to Old Age: A Cross-Sectional Questionnaire Study Among Physicians in the Netherlands - Frédérique W. M. Kraak-Steenken; Frédérique W. M. Kraak-Steenken; Sophie C. Renckens; Sophie C. Renckens; H. Roeline W. Pasman; H. Roeline W. Pasman; Fenne Bosma; Agnes van der Heide; Bregje D. Onwuteaka-Philipsen; Bregje D. Onwuteaka-Philipsen (Frontiers Media S.A., 2024)
Objectives: We explored characteristics of people with an accumulation of health problems related to old age requesting euthanasia or physician-assisted suicide (EAS) and identified characteristics associated with granting EAS requests.Methods: We conducted a cross-sectional questionnaire study among Dutch physicians on characteristics of these people requesting EAS (n = 123). Associations between characteristics and granting a request were assessed using logistic regression analyses.Results: People requesting EAS were predominantly >80 years old (82.4%), female (70.0%), widow/widower (71.7%), (partially) care-dependent (76.7%), and had a life expectancy >12 months (68.6%). The most prevalent health problems were osteoarthritis (70.4%) and impaired vision and hearing (53.0% and 40.9%). The most cited reasons to request EAS were physical deterioration (68.6%) and dependence (61.2%). 44.7% of requests were granted. Granting a request was positively associated with care dependence, disability/immobility, impaired vision, osteoporosis, loss of control, suffering without prospect of improvement and a treatment relationship with the physician >12 months.Conclusion: Enhanced understanding of people with an accumulation of health problems related to old age requesting EAS can contribute to the ongoing debate on the permissibility of EAS in people without life-threatening conditions.